A taxonomic study of the genus Bootania Dalla Torre (Hymenoptera: Torymidae) from China, with description of one new species. (3rd April 2017) - Yao, Qinying; Huang, Dawei; Xiao, Hui
Abstract: The genus Bootania Dalla Torre (Hymenoptera: Torymidae) is reported in China mainland for the first time and one new species Bootania gyacica sp. nov. is described for the first time. Morphological descriptions, distribution, and morphological figures are provided. A key to Chinese species of Bootania is also provided here. Specimens are deposited in the Zoological Museum, Institute of Zoology, Chinese Academy of Sciences. http://zoobank.org/urn:Isid:zoobank.org:pub:AFCA2BAE-EA47-43C3-99F1-F7BE451DAFFC